Effect of dual-scale precipitates on the deformation behavior of AZ41 magnesium alloy via wire-arc directed energy deposition - Yuhang Du; Pubo Li; Hao Ning; Tianle Zou; Yongqiang Zhang; Bintao Wu (Journal of Materials Research and Technology)
With the need for energy saving and emission reduction, the process of wire arc directed energy deposition (WADED) of large-scale, high-precision Mg alloy parts is becoming more widely recognized. However, the poor deformation ability remains a significant challenge that limits its wide application. In this work, the solidification rate and supercooling degree of Mg alloy during WADED process were increased by controlling the interlayer cooling time, and the dispersed micrometer and nanometer dual-scale Al8Mn5 phases were successfully precipitated. The formation mechanism of dual-scale Al8Mn5, microstructural evolution, and their effect on the deformation behavior were comprehensively investigated. The mechanical properties were essentially the same in the build direction and the travel direction, with an average ultimate tensile strength of 236.9 MPa and an elongation of 30.52%. The distribution of double-scale Al8Mn5 impedes the dislocation movement, stimulates the opening of non-basal slip systems, and promotes slip-twinning interactions during plastic deformation. This study offers insights into the design and enhancement of high-performance Mg alloy.